The age of ecology a global history - Radkau, Joachim 1943- (Polity Press, 2014)
This book is the first major study of the history of environmentalism, from its origins in romanticism and the nature cults of the late 18th century to the global environmental movements of today. Radkau shows that this is not a single story of the steady ascent of environmentalism but rather a multiplicity of stories, each with its own dramatic tension: between single-issue movements and the challenges posed by the interconnection of environmental issues, between charismatic leaders and bureaucratic organizations, and between grassroot movements and global players. While the history can be traced back several centuries, environmentalism has flourished since the "environmental revolution" of 1970, spurred on by the Chernobyl nuclear disaster in 1986 and the growing concern about global warming. While environmentalists often opposed the scientific mainstream,they were also often led by scientific knowledge. Environmentalism is the true Enlightenment of our time -- so much so that we can call our era "the age of ecology"--Jacket.